AN ANALYSIS OF STUDENTS` PRONUNCIATION ERRORS AND READING ALOUD ACTIVITY - Nadirah Afifah; Lubis, Yani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
English pronunciation remains a significant challenge for Indonesian EFL learners, particularly in substitution errors where students replace target phonemes with more familiar sounds from their native language. This study investigated substitution error patterns among primary school students aged 10-12 years at a tutoring center in Medan, Indonesia, focusing on errors occurring during reading aloud activities to identify specific phoneme substitutions and understand L1 interference effects on English pronunciation accuracy. A qualitative case study approach was employed with six participants who were recorded reading level-appropriate English texts, with data analyzed using Braun and Clarke's thematic analysis framework and ELSA software for transcription support. The findings revealed three primary error categories: diphthong simplification where students consistently replaced complex English diphthongs (/əʊ/, /eɪ/) with monophthongs, vowel length and quality substitutions reflecting difficulties with English vowel distinctions absent in Indonesian phonology, and consonant voicing errors particularly affecting voiced fricatives and affricates. Notable examples included /nəʊt/ → /nɒt/ for "note," /ˈɡəʊ.ɪŋ/ → /ɡɒn/ for "going," and /ɡɪv/ → /ɡɪf/ for "give," demonstrating systematic L1 phonological interference rather than random pronunciation mistakes. The study concludes that Indonesian EFL learners require explicit, contrastive analysis-based pronunciation instruction targeting specific phonological difficulties, as without targeted intervention, these error patterns are likely to fossilize in learners' interlanguage systems. Future research should examine pronunciation development across different proficiency levels and evaluate the effectiveness of specific teaching techniques addressing identified error patterns.